2022
DOI: 10.3390/cells11020300
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Is the Master Regulator for the Forming of 3D Spheroids of 3T3-L1 Preadipocytes

Abstract: To elucidate the currently unknown mechanisms responsible for the diverse biological aspects between two-dimensional (2D) and three-dimensional (3D) cultured 3T3-L1 preadipocytes, RNA-sequencing analyses were performed. During a 7-day culture period, 2D- and 3D-cultured 3T3-L1 cells were subjected to lipid staining by BODIPY, qPCR for adipogenesis related genes, including peroxisome proliferator-activated receptor γ (Pparγ), CCAAT/enhancer-binding protein alpha (Cebpa), Ap2 (fatty acid-binding protein 4; Fabp4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…In their subsequent study, they also demonstrated that TGF-β2 stimulated EMT in RPE, caused the significant down-regulation of PGC1α, and mitochondrial dysfunctions as well as a metabolic shift towards reduced OXPHOS and increased glycolysis [ 16 ]. In the current study, although we also found that TGF-β2 and hypoxia synergistically and differently induced EMT of the HRPE cells considering the fluctuation in the mRNA expression of HIF1α and the mitochondrial metabolism described above, those fluctuations were also different between 2D and 3D cultures, and such diversity between them may be caused by possible up-stream regulators requiring the generation of the 3D spheroids, as was recently determined using 3T3-L1 cells [ 36 ].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In their subsequent study, they also demonstrated that TGF-β2 stimulated EMT in RPE, caused the significant down-regulation of PGC1α, and mitochondrial dysfunctions as well as a metabolic shift towards reduced OXPHOS and increased glycolysis [ 16 ]. In the current study, although we also found that TGF-β2 and hypoxia synergistically and differently induced EMT of the HRPE cells considering the fluctuation in the mRNA expression of HIF1α and the mitochondrial metabolism described above, those fluctuations were also different between 2D and 3D cultures, and such diversity between them may be caused by possible up-stream regulators requiring the generation of the 3D spheroids, as was recently determined using 3T3-L1 cells [ 36 ].…”
Section: Discussionsupporting
confidence: 60%
“…To study further in terms of the difference between 2D and 3D HRPE cells under several conditions as above, qPCR analysis of the recently determined possible up-stream regulators forming 3D spheroids; STAT3 , IL6 , FOS , TGFb1 , AGT and MYC using 3T3-L1 cells [ 36 ] were studied. As shown in Figure 9 , among these regulators, mRNA expressions of STAT3 , IL6 , FOS and TGF-β1 of the 3D HRPE spheroids were substantially higher than those of the 2D HRPE cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify possible mechanisms responsible for causing such a difference between 2D and 3D cell cultures, RNA sequence analyses were performed. The results suggested that STAT3 functions as the master regulator in forming the 3D spheroid architecture, and related signaling may induce these unique biological differences [ 52 ]. However, as of this writing, the relationship between DIF+ and STAT3-related signaling, as well as diversity in the nature of orbital and other systemic adipocytes, has not been fully investigated.…”
Section: Discussionmentioning
confidence: 99%
“…As a real-time cellular metabolic function analysis, oxygen consumption rate (OCR) and extracellular acidification rate (ECAR) of the 2D-cultured HTM cells in the absence or presence of TGF-β2 (5 ng/mL) and/or ATRA (10 μM) were measured using a Seahorse XFe96 Bioanalyzer (Agilent Technologies, Santa Clara, CA, U.S.A.), as described in a recent report [ 43 , 44 , 45 ]. Briefly, 20 × 10 3 2D HTM cells under several conditions—(1) nontreated control, (2) treated with TGF-β2, (3) treated with ATRA, and (4) treated with TGF-β2 and ATRA—were grown in 96-well assay plates.…”
Section: Methodsmentioning
confidence: 99%